Analisis Faktor-Faktor yang Mempengaruhi Kredit Macet Pada Koperasi Baitul Malwat Tamwil (BMT) Artha Makmur Jaya Bawu - Fifi Fatika Sari; Ali Sofwan (Jurnal Rekognisi Akuntansi, 2018)
Abstract This study aims to determine what factors affect bad loans at the Baitul Malwat Tamwil Cooperative (BMT) Artha Makmur Jaya Bawu. The independent variables (independent) used in this study are character, capital, capacity, collateral, condition and the dependent variable used in this study is bad credit. The research approach used in this research is a quantitative approach. The sampling method was simple random sampling, with the number of respondents being 82 customers. Data collection techniques using a questionnaire in the form of a Likert scale. The analytical technique used is multiple linear regression analysis, taking into account the classical assumption test requirements, namely normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. The hypothesis testing used is a partial statistical test (t test) and a simultaneous statistical test (F test). The results of the t-test indicate that the variables of character, capital, and capacity have a significant effect on bad loans, while the collateral and condition variables have no significant effect on bad loans. F test results show that the independent variables (character, capital, capacity, collateral, and condition) together have a significant influence on bad loans.